З історії міського (само)управління Київської Русі - Ричка, В. (Український історичний журнал, 2021)
Розглядаються питання організації міського управління в Київській Русі. Мета статті полягає у вивченні процесу складання форм міського управління та з’ясуванні компетенції органів общинного (земського) й наказного врядування. Методологічні засади дослідження визначає універсальний принцип історизму з притаманними йому методами герменевтичних процедур і контент-аналізу мовного коду літописних текстів. Наукова новизна. З’ясовано юридичну й політичну ідентичності міських громад Русі. Висновки. Дослідженням не виявлено підтвердження самодостатності вічевих зборів городян. Віче не перетворилося на повноцінний інститут міського самоврядування. Громада могла контролювати діяльність князівської адміністрації, за нею визнавалося право вибору князя, але її адміністративна та судова муніципальна самостійність була обмеженою. Відносини князя й міської громади в києво-руські часи ще не ввібралися в міцні юридичні форми. Власницькі права князя, політична автономія міста, правний статус городян не були захищені імунітетом. Інститут феодального імунітету як форма політичної влади складається у Східній Європі лише на зламі ХІІІ–XIV ст. У цей час дедалі виразнішою стає участь городян у суспільно-політичному житті Галичини та Волині. У містах, де зосереджувався торгово-лихварських капітал, народжувалися якісно нові форми організації й муніципальної юрисдикції громад, що набували окремої юридичної та політичної ідентичності, ставали каталізатором появи в Південно-Західній Русі наприкінці ХІІІ ст. притаманних стандартам європейського Заходу ознак феодалізму. The article considers the organization of city government in Kyivan Rus. Aim of the work is to study the development of forms of municipal government and to clarify the competencies of community (zemstvo) and mandatory government. The methodological principles of the study are determined by the universal principle of historicism with its inherent methods of hermeneutic procedures and the content of the analysis of the language code of chronicle texts. The scientific novelty of the work is to clarify the legal and political identity of the urban communities of Kyivan Rus. Conclusions. The study did not confirm the self-sufficiency of viche meetings of citizens. The viche did not become a full-fledged institution of municipal self-government in Kyivan Rus. The community could control the activities of the prince’s administration and recognized the right to choose a prince, but its administrative and judicial municipal independence was limited. Relations between the prince and the city community in Kyivan Rus times have not yet taken root in strong legal forms. The prince’s property rights, the political autonomy of the city, and the legal status of the citizens were not protected by immunity. The institution of feudal immunity as a form of political power is formed in Eastern Europe only at the turn of thirteenth – fourteenth centuries. At this time, the participation of citizens in the socio-political life of Halychyna and Volyn is becoming more pronounced. Cities in which trade and usurious capital was concentrated, qualitatively new forms of organization and municipal jurisdiction of communities were born, which acquired a separate legal and political identity and became a catalyst for the emergence of South-Western Rus in the late thirteenth century, inherent in the standards of the European West signs of feudalism.